Temporal discounting across three psychiatric disorders: Anorexia nervosa, obsessive compulsive disorder, and social anxiety disorder. Issue 5 (23rd December 2016) - Steinglass, Joanna E.; Lempert, Karolina M.; Choo, Tse‐Hwei; Kimeldorf, Marcia B.; Wall, Melanie; Walsh, B. Timothy; Fyer, Abby J.; Schneier, Franklin R.; Simpson, H. Blair
Abstract : Background: Temporal discounting refers to the tendency for rewards to lose value as the expected delay to receipt increases. Individuals with anorexia nervosa (AN) have been found to show reduced temporal discounting rates, indicating a greater preference for delayed rewards compared to healthy peers. Obsessive–compulsive disorder (OCD) and social anxiety disorder (SAD) commonly co‐occur with AN, and anxiety has been related to development and prognosis of AN. We examined whether reduced temporal discounting is present across these potentially related disorders, and explored the relationship between temporal discounting and anxiety transdiagnostically. Methods: One hundred ninety six individuals (75 healthy controls (HC); 50 OCD; 27 AN; 44 SAD) completed two temporal discounting tasks in which they chose between smaller‐sooner and larger‐later monetary rewards. Two measures of discounting—discount rate and discount factor—were compared between diagnostic groups, and associations with anxious traits were examined. Results: Individuals with AN showed decreased temporal discounting compared to HC. OCD and SAD groups did not differ significantly from HC. Across the sample, anxiety was associated with decreased discounting; more anxious individuals showed a greater preference for delayed reward. Conclusions: We replicated the findings that individuals with AN show an increased preference for delayed reward relative to HC and that individuals with OCD do not differ from HC. We also showed that individuals with SAD do not differ from HC in discounting. Across this large sample, two measures of anxious temperament were associated with temporal discounting. These data raise new questions about the relationship between this dimensional trait and psychopathology.